Study of Synthesis and Characterization of Metal-Organic Frameworks MOF-5 as Hydrogen Storage Material - Prapti Rahayu; Witri Wahyu Lestari (ALCHEMY Jurnal Penelitian Kimia, 2016)
Metal-organic frameworks (MOFs) are porous coordination polymer containing bi-or polidentate organic linker coordinated with inorganic part, such as metal oxide cluster or metal cation as node which called as secondary building unit (SBU) to form infinite structure. Due to high porosity and surface area, good thermal stability as well as the availability of unsaturated metal center or the linker influence attracts the interaction with gases, thus MOFs have potential to be applied as hydrogen storage material. One type of MOFs that have been widely studied is [Zn4O(benzene-1,4-dicarboxylate)3], namely, MOF-5.Various synthesis method have been developed to obtain optimum results. Characterization of MOF-5 from various synthesis method such as crystallinity, capacity, stability, and quantum dot behavior of MOF-5 have been summarized in this review.